Enhancing farm productivity and profitability with Farmer FIRST Programme, focus at Khordha district of Odisha - Patra, Alok Kumar; Mishra, Prasannajit; Mohapatra, Bijay Kumar; Roul, Pravat Kumar; Sahoo, Abinita (Indian Farming, 2025)
The Farmer FIRST Programme (FFP) implemented by Odisha University of Agriculture and Technology (OUAT) in six villages of Khordha district has significantly enhanced agricultural productivity, profitability, and socio-economic conditions of farmers. The programme adopted an integrated module approach involving field crops, horticulture, livestock, enterprises, and resource based activities. Interventions included replacement of traditional paddy varieties with high-yielding ones, off-season vegetable cultivation, improved livestock management, and promotion of mushroom and small-scale enterprises. These efforts led to yield increases of 23–87% in paddy and 33–116% in vegetables, and income gains ranging from 70–467%. Dairy, goatery, and backyard poultry modules recorded substantial improvements in productivity and profitability. The project also empowered women through resource-based enterprises like dal and flour mills, enhancing their income sources. Socio-economic impact analysis revealed marked improvements in farmers’ participation, contact with extension agencies, decision-making ability, and social security. Case studies demonstrated income enhancement up to 215%, showcasing the success of FFP interventions in transforming smallholder livelihoods and promoting sustainable, inclusive growth in the region.